Penerapan Metode MAUT dalam Penentuan Karyawan Berprestasi dengan Pembobotan ROC - Dimas Hadityo Ramadan; Mesran Mesran; Rian Syahputra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
PT. Gruti Lestari Pratama Mandailing Natal is part of the Mujur Group which was founded on May 1, 1996 with a head office in Medan and oil palm plantations and a palm oil mill located in Mandailing Natal, North Sumatra. In an effort to improve the performance of the employees, PT. Gruti Lestari Pratama Mandailing Natal determines the outstanding employees every year. The purpose of determining outstanding employees is to improve the performance of each employee which can support the progress of the company. In determining outstanding employees, PT. Gruti Lestari Pratama Mandailing Natal evaluates only one assessment, namely achievement, even though there are several other criteria that can be used as criteria for determining outstanding employees such as discipline, responsibility, achievement, cooperation, attendance and letters of reprimand. Some of these criteria will be a more effective assessment of the previous assessment of the determination of outstanding employees at PT. Gruti Lestari Pratama Mandailing Natal. In determining outstanding employees, a decision support system (SPK) is needed. SPK in this study uses the MAUT method with ROC weights. The result of the best alternative decision is the A9 alternative on behalf of